Effects of parental larval diet on egg size and offspring traits in Drosophila - Vijendravarma, Roshan K. (The Royal Society, 2010)
If a mother's nutritional status predicts the nutritional environment of the offspring, it would be adaptive for mothers experiencing nutritional stress to prime their offspring for a better tolerance to poor nutrition. We report that in Drosophila melanogaster, parents raised on poor larval food laid 3–6% heavier eggs than parents raised on standard food, despite being 30 per cent smaller. Their offspring developed 14 h (4%) faster on the poor food than offspring of well-fed parents. However, they were slightly smaller as adults. Thus, the effects of parental diet on offspring performance under malnutrition apparently involve both adaptive plasticity and maladaptive effects of parental stress.